Final energy calibration at LEP 1 - Wilkinson, G (1998)
The determination of the collision energy is a crucial ingredient in the LEP measurement of the mass and width of the Z° resonance. This energy calibration has recently been finalised for the 1993-1995 data sets. The key aspects of the analysis are summarised, and the new understanding gained during the 1995 scan is discussed.